X-RAYS SEPARATOR: FORWARD STEP IN TECHNOLOGY OF OPTICAL SEPARATION - N. N. Potrakhov; S. L. Beletskiy; F. B. Musaev (Овощи России, 2017)
Presently the X-ray separation is used not only for research program, but it is also elaborated and applied for different sectors of economy. The seeds as biological objects that possess the complicated microstructure are very difficult to be exanimated by x-ray technology. The application of x-rays and further elaboration of optical  separators, principle  of action, basic specifications, way of their use and their efficiency was shown in the article. The x-ray separator may distinguish all hidden seed defects as it was described by a programmer, where owing to the use of the optical separating block in visual range it is possible to add some more details as a shape, brightness and a color of object surface being exanimated. The elaboration of such separation equipment is scientifically hard work requiring time and expenses. Last year researchers of ‘LETI’ developed the working model of industrial x-ray separator for examination of grains and nuts in different crops. This model was made on the basis of photoseparator F-5 manufactured at OAO ‘Voronezhselmash’. The instrument state and its mechanism operation are highlighted on monitor. In the regime of processing (separation and examination) of each controlled batch, the passport is produced with  following  information on identification  code,  time of material receiving, time of test passed, number of grains or seeds tested. The code of receiver of material is given to each of established characteristics when working the regime of separation, determination of number of objects with characteristics tested and number of unidentified objects. The application of x-ray separators constructed on the basis of photoseparator F-5 enables to carry out the complex estimation on seed quality and separation in only instrument with the development of electronic protocol with many characteristics.